AN ANALYSIS OF STUDENTS’ SPEAKING ANXIETY IN PUBLIC SPEAKING CLASS IN ENGLISH DEPARTMENT OF UNIVERSITAS NEGERI SURABAYA (RETAIN, 2016)
AN ANALYSIS OF STUDENTS’ SPEAKING ANXIETY IN PUBLIC SPEAKING CLASS IN ENGLISH DEPARTMENT OF UNIVERSITAS NEGERI SURABAYA IRMA NURLAILI English Education, Language and Art Faculty, State University of Surabaya irmanurlaili@mhs.unesa.ac.id ESTI KURNIASIH, S. Pd., M. Pd. English Education, Language and Art Faculty, State University of Surabaya estikurniasih@unesa.ac.id Abstrak Penelitian ini bertujuan untuk mendeskripsikan komponen-komponen kegugupan berbicara yang teridentifikasi dalam Kelas Public Speaking, mendeskripsikan penyabab-penyebab mengapa siswa merasa gugup, dan mendeskripsikan solusi untuk mengatasi dan mengurangi kegugupan berbicara dalam Kelas Public Speaking. Penelitian ini adalah penelitian deskriptif kualitatif. Peneliti menganalisis data secara kualitatif. Subjek dari penelitian ini adalah mahasiswa-mahasiswa Pendidikan Bahasa Inggris Universitas nNegeri Surabaya yang berada di semester IV dan mengambil Kelas Public Speaking. Data diperoleh melalui pengamatan. Peneliti menggunakan field note, lembar pengamatan, wawancara, dan Foreign Language Classroom Anxiety Scale (FLCAS) untuk membantu peneliti memperoleh data. Berdasarkan hasil yang diperoleh, dapat disimpulkan bahwa ada 3 (tiga) komponen kegugupan berbicara yaitu communication apprehensions, test anxiety, dan also fear of negative evaluation. Kegugupan berbicara terjadi karena beberapa penyebab. Peneliti menemukan hanya ada 3 (tiga) penyebab kegugupan berbicara yaitu personal and interpersonal, classroom procedures, dan language test. Kemudian, untuk menyelesaikan permasalahan ini, peneliti menemukan 5 (lima) solusi untuk mengatasi dan mengurangi kegugupan berbicara yaitu planning for change, confronting anxiety-provoking situation, changing the way to communicate and improve the relationships, learning to make presentation with confidence, dan stop trying to be perfect. Kata kunci: kegugupan, kegugupan berbicara, speaking di depan umum Abstract This research is aimed to describe the components of speaking anxiety which are classified in Public Speaking Class, describe the causes why the students feel anxious, and describe the solution to overcome and reduce the speaking anxiety in Public Speaking Class. This study is a descriptive qualitative study. The researcher analyzed the data qualitatively. The subjects of the study are college students in English Department of Universitas Negeri Surabaya who are in the fourth semester and take Public Speaking Class. The data was obtained by doing observation. The researcher used field notes, observation checklist, interview guide, and Foreign Language Classroom Anxiety Scale (FLCAS) to help her obtain the data for the research. Based on the data result, it can be concluded that there are 3 (three) components of students speaking anxiety in Public Speaking Class. They are communication apprehensions, test anxiety, and also fear of negative evaluation. The speaking anxiety happened because of some reasons. The researcher found only 3 (three) causes of speaking anxiety. They are personal and interpersonal, classroom procedure, and language test. Then, to solve this problem, the researcher found 5 (five) solutions to overcome and reduce speaking anxiety. They are planning for change, confronting anxiety-provoking situation, changing the way to communicate and improve the relationships, learning to make presentation with confidence, and stop trying to be perfect. Keywords: anxiety, speaking anxiety, public speaking.